Marketing Communication Strategy for Tourism Sidoarjo in Developing Regional Tourism Potential - Bagus Waskita Rama; Kukuh Sinduwiatmo (Indonesian Journal of Public Policy Review, 2022)
This study aims to determine the marketing communication strategy carried out by the tourism sector DISPORAPAR Sidoarjo. This study used descriptive qualitative method. The object of this research is the marketing activities of the DISPORAPAR tourism sector in the city of Sidoarjo. In carrying out marketing communication strategies to tourist visits. The process of data collection was carried out by means of observation, in-depth interviews and documentation. The results showed that (1) During the Covid-19 pandemic the number of tourists visiting Sidoarjo decreased by 50% from the previous year 2019. In addition, in the last 3 years Sidoarjo tourism experienced a decrease in tourist visitors. There are only a few who experienced an increase in the number of visitors. (2) Communication strategy in the tourism sector DISPORAPAR Sidoarjo City in increasing tourist visits, namely by carrying out various forms of marketing communication such as through Advertising, personal selling, Publicity and Public Relations and Direct Marketing.